The Taḥlīl al-Akhtā' al-Luġawiyyah Fī Kitābah al-Insyā' Ladā Ṭalabah ma'had Gontor Darussalam - Bin Zaid, Abdul Hafiz; Nurfadillah, Siti; Fitri Islami, Diana; Aina Najiah, Safira; Mubarak, Faisal; Bkheet Ahmed, Bakri Mohamed (UIN ANTASARI, 2024)
Abstract The aim of Arabic language education is to help students master language skills and foster positive changes in their attitudes and behaviors. The success of teaching can be measured through the improvement in listening, speaking, reading, and writing skills. Writing, particularly Insya (composition), is often viewed as challenging for non-native speakers and requires detailed study to achieve proficiency. Errors in written Arabic, especially in grammar and spelling, are often judged more critically than oral mistakes. This research investigates linguistic errors in the Insya of fifth-grade students at Darussalam Gontor Modern Islamic Boarding School Campus 1. Using a linguistic taxonomy model, errors were classified in areas like phonology, syntax, morphology, and semantics. Five major types of errors were identified, including adjective-noun agreement, diacritical marks, and the use of direct objects. The study employed a qualitative descriptive approach, using student compositions as data, and emphasized the need to address these errors to improve students' Arabic writing proficiency. Keyword: Language Error Analysis, Insya ’